2016
DOI: 10.1364/boe.7.003262
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diffuse correlation tomography reveals spatial and temporal blood flow differences in murine bone grafting approaches

Abstract: Longitudinal blood flow during murine bone graft healing was monitored non-invasively using diffuse correlation tomography. The system utilized spatially dense data from a scanning set-up, non-linear reconstruction, and micro-CT anatomical information. Weekly measurements were performed. Blood flow changes in autografts, which heal successfully, were localized to graft regions and consistent across mice. Poor healing allografts showed heterogeneous blood flow elevation and high inter-subject variabilities. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…This limitation resulted in the lack of blood flow information during the tumor growth prior to treatment. To address these limitations, a non-contact scanning diffuse correlation tomography system [72,73] will be adapted for animal cancer monitoring. This will enable measurements of tumors at any time during their development and provide reliable three-dimensional blood flow imaging with spatially dense datasets from the scanning system.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…This limitation resulted in the lack of blood flow information during the tumor growth prior to treatment. To address these limitations, a non-contact scanning diffuse correlation tomography system [72,73] will be adapted for animal cancer monitoring. This will enable measurements of tumors at any time during their development and provide reliable three-dimensional blood flow imaging with spatially dense datasets from the scanning system.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%
“…In our laboratory, a noncontact DCT technique has been developed for assessing blood flow in a murine femoral graft model. The DCT technique has been verified and applied in previous tissue phantom and longitudinal bone graft monitoring studies . In our weekly bone graft measurements, blood flow in grafts increased at one week after graft surgery.…”
Section: Introductionmentioning
confidence: 60%
“…Estimation of the blood flow distribution αD b ( r ) based on the measured g 2 on tissue surface is determined by minimizing the objective function χ2=12false∑i=1Nsd||ln)(g1,mbold-italicritalicsi,bold-italicritalicdi,τg1,cbold-italicritalicsi,bold-italicritalicdi,τ2 . Here, g 1,c is the calculated autocorrelation function based on an estimate of blood flow distribution, g 1,m is the experimentally obtained autocorrelation function, N sd is the total number of the source‐detector pairs, and r si and r di are the locations of the source and detector.…”
Section: Methodsmentioning
confidence: 99%
“…DCT has been studied in both preclinical and clinical settings to monitor blood flow changes in mouse and rat brains [ 14 , 15 ], and in human breast [ 16 ]. We have developed a non-invasive DCT system to monitor 3-dimensional blood flow changes in the mouse femur [ 17 , 18 ]. With the DCT system, we have revealed that blood flow changes are different among three groups of autografts, allografts, and T.E.…”
Section: Introductionmentioning
confidence: 99%
“…Weekly DCT measurements were performed on three groups of mice for 9 weeks, adhering to the same protocol reported previously [ 17 ]. To independently quantify graft healing, we utilized an established biomechanical testing method to measure maximum bone torque after 9-week healing, which has been widely used as an indicator for long-term healing [ 6 , 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%